Genetic Relationships Between Grain Types and Agronomic Traits In Rice - Sugiono Moeljopawiro (Zuriat, 2002)
The genetic relationships between grain types and agronomic traits in rice (Oryza sativa L.) were studied in 6 x 6 diallel cross (excluding reciprocals) involving long-, medium-, and short-grain cultivars were studied. Combining ability analyses revealed that mean squares due to GCA were larger than those due to SCA, except for heading date. Vsca for heading date, plant height, panicle number, and grains per panicle were larger than Vgca for those traits. Panicle length, grain length, grain width, and 100-grain weight had larger Vgca than Vsca. General combining ability effects obtained in this study suggested that ‘Brazos’ was a good combiner for earliness. ‘Starbonnet’ was a good combiner for plant height, grains per panicle, and ‘Starbonnet’ and ‘Lebonnet’ were good combiners for grain length. ‘Nortai’ combined well for high panicle number and ‘Nortai’ and ‘S201’ combined well for grain width. ‘M401’ and ‘S201’ were good combiners for 100-grain weight. Phenotypic and genetic correlations followed a similar trend, except the latter was of a higher magnitude. Grain width and 100-grain weight were positively correlated with each other, but negatively correlated with the other traits. Grain length and grain width were negatively correlated. In general, heritability estimates in the broad sense were high. Moderate narrow sense heritability estimates for plant height, panicle length, grain length, grain width, and 100-grain weight suggested that these traits can be selected with the pedigree method, and the bulk method would be better for selecting heading date and grains per panicle.